A regional synergy approach to energy recovery: The case of the Kwinana Industrial Area, Western Australia - Van Beers, Dick; Biswas, Wahidul (Elsevier Science Limited, 2008)
Energy is a key issue in the Kwinana Industrial Area, Western Australia's major heavy industrial region, where the major energy consuming industries consume up to 80 PJ/yr of energy in their processes. Over the past decade, significant progress has been made towards the reduction of energy consumption and reduction of greenhouse gases in Kwinana. One way to further advance sustainable energy use is through the realisation of regional synergies. These concern the capture, recovery and reuse of by-products,water and energy between industries in close proximity. Kwinana is recognised as a leading edge example in regional synergy development, but more synergy opportunities appear to exist. The Centre for Sustainable Resource Processing (CSRP) is undertaking research to develop new synergies in Kwinana, including energy utility synergies. As part of the research, a methodology was developed and applied to identify and evaluate the economic, technical, and environmental feasibility of collaborative energy recovery opportunities from industry flue gases in Kwinana. The trial application demonstrated the significant potential to mitigate CO2 emissions through energy recovery from fluegases by applying technologies to convert the embedded energy into useful thermal andelectric applications. This article discusses the methodology and outcomes from the trialapplications, including the impact of carbon taxes, reducing costs of emerging technologies, and increasing energy prices.